Shin Splint: The Complexities of a Common lower Leg Affliction - Han, Haolun (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In the realm of sports, fitness, and physical activities, shin splints are closely connected with athletes, runners, and ballers. The discomfort and pain associated with the athlete spirit bring about the worst feeling when facing challenges in recovery. This essay delves deep into the area of shin splints, pointing out the intricate web of factors that contribute to the development and impact on individuals who are working on and trying to overcome the pain. Besides, the review Includes more detailed insights into the physiological and biomechanical aspects of shin splints, discuss the latest research findings on effective treatment and prevention methods, and highlight the implications of shin splints on athletes’ performance and recovery processes. The essay also explores various strategies for prevention and management, taking an interdisciplinary approach to understand and address the condition. This review can provide valuable information and reference for the treatment, rehabilitation, and prevention of tibial splints.